Recurrent abortion: etiology and care (Research, Society and Development, 2020)
Objective: this article aims to discuss the main aspects related to recurrent abortion and preventive care and to characterize the importance of prenatal care in preventing recurrent abortion. Method: This is a qualitative study of an explanatory character through an integrative literature review, which is a method that provides knowledge and results of studies in practice, with a broad methodological approach incorporating concepts, review of theories, evidence and analysis of methodological problems. Results: recurrent abortion can be of different etiologies, however, 40 to 60% of recurrent abortions are of identifiable or idiopathic causes due to the fact that they are not linked to any disease or perhaps due to lack of investigation. Conclusion: recurrent pregnancy losses are multifactorial, and can occur due to abnormalities in the chromosomes and uterus, infections and causes that can be considered as identifiable because they are not linked to a specific disease. However, prenatal care is of great importance in preventing recurrent spontaneous abortion, as it plans to reduce risks and guarantee the well-being of women during their pregnancy.